IMPLEMENTASI PERATURAN BUPATI SUMEDANG NO.180 TAHUN 2022 TENTANG APLIKASI SINDANG DI DINAS KOPERASI, UMKM, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN SUMEDANG - Mardiani, Sulastri (JRPA - Journal of Regional Public Administration, 2025)
This research aims to understand the implementation of Sumedang Regent Regulation No. 180 of 2022 regarding the Application-Based Trade Information System (SINDANG) at the Office of Cooperatives, Micro, Small and Medium Enterprises, Trade, and Industry of Sumedang Regency. The research method employed is qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation to gather information related to policy implementation. The results indicate that the implementation of SINDANG has commenced but is not yet optimal. The communication dimension reveals clear information dissemination through social media, while human resources are still inadequate, particularly in terms of skills. Employee disposition shows support for the application, although there are challenges in technology adaptation. The bureaucratic structure has been established, but its implementation is hindered by limited facilities. Identified hindering factors include a lack of understanding of the policy, varying stakeholder support, and the need for resource enhancement. Efforts made to improve implementation include regular socialization, training, and inter-departmental collaboration. This study recommends greater attention from local government in providing resources and facilities to support the successful implementation of SINDANG.